Answer:
see below
Explanation:
a
y = 2x -3
Standard form is Ax + By =C where A is a positive integer and B and C are integers
Subtract 2x from each side
y-2x = 2x-2x -3
-2x+y = -3
We want A to be positive
Multiply each side by -1
2x -y = 3
This is in standard form
b
y = 2/3 x -7
Subtract 2/3x from each side
y-2/3x = 2/3x-2/3x -7
-2/3x+y = -7
We want A to be positive integer
Multiply each side by -3
-3*(-2/3x+y) = -7*-3
2x -3y = 21
c
y = -3x +1/2
Add 3x to each side
3x +y = -3x+3x +1/2
3x+y = 1/2
Multiply each side by 2
2(3x+y) = 1/2*2
6x+2y = 1